User Generated Content as a Moderating Variable of the Influence of Brand Trust on Customer Satisfaction: Penelitian - Johannes P. Kumagaya; Jeanne Senduk; Rudy Irwansyah; Bambang Amir Alhakim; Franciscus Dwikotjo Sri Sumantyo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Increasingly fierce market competition, driven by digitalization and social connectivity, places Brand Trust as the most critical non-financial asset an organization possesses. Brand Trust has long been proven to directly influence Customer Satisfaction because it reduces risk and uncertainty in purchasing decisions and service usage. However, the digital era has introduced a new dynamic variable, namely User Generated Content (UGC)- content created by consumers (such as reviews, testimonials, unboxing vlogs , and social media comments) rather than by the brand itself—which serves as a source of information that is inherently perceived as more credible and authentic. This study aims to examine and analyze the role of UGC as a moderating variable in the causal relationship between Brand Trust and Customer Satisfaction, specifically in the context of the [Specify specific context, e.g., e-commerce or hospitality industry] market. Using a quantitative approach with a hierarchical regression model (Moderated Regression Analysis), this study tests the hypothesis that the positive impact of Brand Trust on Customer Satisfaction will be strengthened (positive moderation) when Customers are exposed to high and consistent volume and quality of UGC, or conversely, the impact can be weakened by negative UGC.